The influence of soil and biosolids type, and microbial immobilisation on nitrogen availability in biosolids-amended agricultural soils - implications for fertiliser recommendations - Rigby, Hannah; Perez-Viana, F.; Cass, J.; Rogers, M.; Smith, S. (WILEY-BLACKWELL PUBLISHING, INC, 2009)
Soil microbial biomass interactions influencing the mineralisation of N in biosolids-amended agricultural soil were investigated under field conditions in two soil types, a silty clay and a sandy silt loam, with contrasting organic matter contents. Soil treatments included: dewatered raw sludge (DRAW); dewatered and thermally dried, mesophilic anaerobically digested biosolids (DMAD and TDMAD, respectively); lime-treated unstabilised sludge cake (LC); and NH4Cl as a mineral salt control for measuring nitrification kinetics. Soil mineral N and microbial biomass N (MBN) concentrations were determined over 90 days following soil amendment. Despite its lower total and mineral N contents, TDMAD had a larger mineralisable pool of N than DMAD, and was an effective rapid release N source. Increased rates of mineralisation and nitrification of biosolids-N were observed in the silty clay soil with larger organic matter content, implying increased microbial turnover of N in this soil type compared with the sandy silt loam, but no significant difference in microbial immobilisation of biosolids- N was observed between the two soil types. Thus, despite initial differences observed in the rates of N mineralisation, the overall extent of N release for the different biosolids tested was similar in both soil types. Therefore, the results suggest that fertiliser guidelines probably do not need to consider the effect of soil type on the release of mineral N for crop uptake from different biosolids products applied to temperate agricultural soils.